1994
DOI: 10.1161/01.str.25.11.2142
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour beta-endorphin secretory pattern in stroke patients.

Abstract: Background and Purpose Abnormalities of hypothalamopituitary-adrenocortical axis function have been observed frequently in stroke patients. The aim of this study was to investigate plasma /S-endorphin and cortisol 24-hour secretory patterns in patients early after stroke and in the convalescent period to evaluate a possible influence of brain damage on hormonal circadian pattern.Methods Patients (n=15; age, 46 to 75 years) were evaluated in the first 24 hours and 10 days after hospital admission for ischemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Abnormalities in various hormonal systems, particularly in the hypothalamic-pituitary-adrenal axis with increased activity [28, 29, 30, 31], are described after early stroke. A high level of cortisol is found in patients with acute stroke compared to age- and sex-matched healthy normal controls [32, 33, 34]. About 70% of patients in this study had high and/or abnormal cortisol levels, and these patients had a statistically significantly higher SBP than patients with normal cortisol levels.…”
Section: Discussionmentioning
confidence: 70%
“…Abnormalities in various hormonal systems, particularly in the hypothalamic-pituitary-adrenal axis with increased activity [28, 29, 30, 31], are described after early stroke. A high level of cortisol is found in patients with acute stroke compared to age- and sex-matched healthy normal controls [32, 33, 34]. About 70% of patients in this study had high and/or abnormal cortisol levels, and these patients had a statistically significantly higher SBP than patients with normal cortisol levels.…”
Section: Discussionmentioning
confidence: 70%
“…Single measurement s-cortisol was chosen as a previous study has shown that a circadian rhythm cannot be demonstrated in acute stroke [18]. …”
Section: Methodsmentioning
confidence: 99%
“…It has also been observed that the normal circadian rhythm of cortisol is suspended during acute stroke as equal levels of cortisol were found round the clock [15].…”
Section: Introductionmentioning
confidence: 99%